Biochemistry and adaptive colouration of an exceptionally preserved juvenile fossil sea turtle. Issue 1 (December 2017) - Lindgren, Johan; Kuriyama, Takeo; Madsen, Henrik; Sjövall, Peter; Zheng, Wenxia; Uvdal, Per; Engdahl, Anders; Moyer, Alison E.; Gren, Johan; Kamezaki, Naoki; Ueno, Shintaro; Schweitzer, Mary
Abstract The holotype (MHM-K2) of the Eocene cheloniineTasbacka danica is arguably one of the best preserved juvenile fossil sea turtles on record. Notwithstanding compactional flattening, the specimen is virtually intact, comprising a fully articulated skeleton exposed in dorsal view. MHM-K2 also preserves, with great fidelity, soft tissue traces visible as a sharply delineated carbon film around the bones and marginal scutes along the edge of the carapace. Here we show that the extraordinary preservation of the type ofT .danica goes beyond gross morphology to include ultrastructural details and labile molecular components of the once-living animal. Haemoglobin-derived compounds, eumelanic pigments and proteinaceous materials retaining the immunological characteristics of sauropsid-specific β-keratin and tropomyosin were detected in tissues containing remnant melanosomes and decayed keratin plates. The preserved organics represent condensed remains of the cornified epidermis and, likely also, deeper anatomical features, and provide direct chemical evidence that adaptive melanism – a biological means used by extant sea turtle hatchlings to elevate metabolic and growth rates – had evolved 54 million years ago.